Enamel defect of deciduous teeth in small gestational age children - Willyanti S Syarif; Roosje R. Oewen; Sjarif H. Effendi; Bambang Sutrisna (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Enamel defect could be caused by genetic and environmental factors in prenatal period. Meanwhile, prenatal malnutrition could also cause small gestational age (SGA). Small Gestational Age is the term used for a neonatal baby with birthweight below the -2SD normal value or 10th percentile on the intrauterine Lubchenco curve. This condition is due to intra-uterine growth restriction, and eventually ends up with several developmental defects of organs, including teeth. In fact, deciduous tooth development has a critical phase within this development period. Purpose: The aim of this study is not only to find out the incidence of enamel defect in SGA children, but also to know the percentage of SGA risk factor to develop enamel defect. Method: This was a epidemiology research with consecutive admission technique. It consisted of 153 SGA children aged 9–48 months. Next, the Ponderal index was used to assign SGA types, symmetrical or asymmetrical one-in this study 59 and 94 respectively. On the other hand, three hundred and ninety Appropriate for Gestational Age (AGA) children aged 4–48 months were also included in the study as a control group. Enamel defect then was determined by intraoral examination, classified into hypoplasia and hypocalcifications. Chi-square test was finally used to determine the relative risk ratio between the SGA and the control AGA children. Result: The result of this research showed that incidence of enamel defect in SGA children was 86.92%, meanwhile, that in AGA children was 23.08%, 66.00% of which were commonly suffered from hypocalcification. With p<0.05 it is also known that SGA children has the risk of enamel defect with hypocalcification, about 79% higher than AGA children. Conclusion: It could be concluded that 79% of SGA children had the risk of deciduous tooth enamel defect with hypocalcification as the most.Latar belakang: Defek email dapat terjadi karena faktor genetik dan lingkungan sistemik yang terjadi saat prenatal. Adanya malnutrisi prenatal dapat mengakibatkan kelahiran bayi dengan kecil masa kehamilan. Kecil masa kehamilan (KMK) adalah bayi dengan berat badan lahir di bawah -2SD nilai normal atau dibawah persentil 10 kurva pertumbuhan intra uterin Lubchenco. Kondisi ini terjadi sebagai akibat intra uterine growth restriction (IUGR) yang mengakibatkan defek perkembangan organ tubuh, termasuk gigi sulung karena masa kritis pertumbuhan dan perkembangan gigi sulung terjadi pada periode prenatal. Tujuan: Tujuan penelitian ini adalah untuk mengetahui insidensi defek email gigi sulung pada anak KMK dan mengetahui besarnya risiko KMK untuk terjadinya defek email pada gigi sulungnya. Metode: Disain penelitian adalah epidemiologi dengan consecutive admission. Sample terdiri dari 153 anak KMK berusia 9–48 bulan. Diperoleh 59 tipe simetri dan 94 tipe asimetri dengan indeks Ponderal. Sebagai kontrol diperiksa 390 anak Sesuai masa kehamilan (SMK) berusia 4–48 bulan. Pemeriksaan intra oral dilakukan untuk melihat ada tidaknya defek. Tipe defek adalah hipoplasia dan hipokalsifikasi. Uji Chi-kuadrat digunakan untuk menguji risiko relatif defek email pada anak KMK dan SMK. Hasil: Hasil penelitian menunjukkan insidensi defek email pada anak KMK sebesar 86,92% dan pada anak dengan sesuai masa kehamilan (SMK) sebesar 23,08%, dengan jumlah defek terbanyak adalah hipokalsifikasi sebanyak 66,60%. Dengan p < 0,05 anak KMK berisiko 79% untuk mengalami defek email gigi sulung. Kesimpulan: Dari penelitian ini disimpulkan bahwa anak KMK berisiko 79% mengalami defek email gigi sulung dengan tipe defek terbanyak adalah hipokalsifikasi.